Analisis Pelaksanaan Program Keluarga Harapan di Desa Bandar Sono Kecamatan Nibung Hangus Kabupaten Batu Bara. - Elvira Santi; Mbina Pinem (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
This study aims to determine (1) the requirements of recipients of the family hope program (2) the implementation of the family hope program in education (3) the implementation of the family hope program in the health sector. This research was carried out in Bandar Sono Village in 2019. The population in this study were all residents in Bandar Sono village who had implemented the Hope Family Program of 442 KPM (Beneficiary Families). The sample is determined 20% of the total population so that the sample is 88 KPM. Data collection techniques used were direct communication / interview techniques. Data were analyzed using qualitative descriptive techniques. The results showed (1) Requirements for recipients of the hope family program in Bandar Sono village did not fully qualify as recipients of the hope family program because there were 12 KPM that were not included in poor households. (2) Implementation of the family of hope program in the field of education with attendance of more than 85% of the effective days of school every month. Thus the implementation of the family of hope program in the field of education has been going well. (3) the implementation of the family hope program in the health sector has run well and all participants of the family hope program have been helped in meeting the needs in the health sector.